Fighting for Space Within the Cis‐ and Heteronormative Public Sphere: An Analysis of Budapest Pride - Alexandra Sipos; Márton Bagyura (Social Inclusion, 2024)
The article presents the urban space use of the LGBTQI+ community in a post‐socialist and illiberal country, Hungary, by focusing on the historical development of Pride marches within the capital. Examining these events’ routes, current regulations, and resistance related to Pride, the article observes acts of silencing and the disruption of silencing concerning the LGBTQI+ community. First, we rely on sexual and intimate citizenship studies (e.g., Plummer, 2003; Richardson, 2017) to highlight the public/private divide and related (in)visibility and human rights issues associated with the LGBTQI+ community within a cis‐ and heteronormative environment. Second, queer geography and the geography of sexualities are used to better understand the cis‐ and heteronormative environment within which sexual and gender minorities exist and operate. Regarding the Hungarian context, we assume that “a gradual extension of public space use” is present concerning the public events of the LGBTQI+ community in Hungary (Takács, 2014, p. 202). The article analyzes three aspects concerning the Pride parades held in Budapest through the 3R analytical lens and connected silencing and the disruption of silencing: the spatial routes of the Budapest Pride, related regulations, and the resistance to and of LGBTQI+ visibility in an urban setting. First, through maps, we visualize the routes of the Budapest Pride parades from 1997 to 2022 to understand how the visibility of LGBTQI+ and allies is constricted and regulated in the spatial dimension. Second, following the regulatory approach of the Budapest Pride organization, we focus on how the police ensure these events’ and attendees’ safety and whether cordons—physical symbols of division between participants, police, and bystanders or protesters—are necessary. The third aspect elucidates the resistance against and toward the visibility of LGBTQI+ people in the urban setting.